Composite current collector and preparation method thereof, and negative electrode-free lithium battery
By using a composite fluid collection in a negative electrode-free lithium battery, the first artificial SEI layer including a high entropy alloy and an oxide solid electrolyte layer, the problem of uneven deposition of lithium metal is solved, and the circulation performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411509320.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
During the charging and discharging process of negative electrode lithium batteries, the deposition and peeling of lithium metal on the negative electrode current collector is uneven, resulting in irregular growth of lithium dendrites, causing SEI film rupture and harmful side reactions at the interface, affecting battery safety and cycle life.
Using a composite fluid collection, including a metal substrate and a first artificial SEI layer disposed on the metal substrate, the first artificial SEI layer consists of a high entropy alloy layer and an oxide solid electrolyte layer, and the high entropy alloy layer is disposed on the metal substrate and the oxide Between the solid electrolyte layers, the high-entropy alloy layer contains at least 2 magnetic elements and 4 lithium-philic elements. The oxide solid electrolyte layer has the ability to conduct ion, promotes rapid transport of lithium ions and reduces migration impedance.
Through the use of composite fluid collection, the compact deposition and uniform nucleation growth of lithium metal are promoted, the cyclic electrochemical performance of the battery is improved, and the stability and safety performance of the battery are enhanced.
Smart Images

Figure CN119029215B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a composite current collector and a preparation method thereof, and a negative electrode-free lithium battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, low self-discharge rate, and no memory effect, so they are widely used. The negative electrode of traditional lithium batteries is usually composed of materials such as graphite, silicon carbon, lithium metal or lithium-containing compounds. However, negative electrode-free lithium batteries do not use negative electrode materials during the production process. During the first charge, lithium ions are released from the positive electrode material, migrate to the negative electrode collector through the electrolyte, obtain electrons and deposit to form a lithium metal layer. During the discharge process, lithium metal loses electrons and becomes lithium ions. The lithium ions return to the positive electrode through the electrolyte again, completing a charge and discharge cycle.
[0003] However, during the charging and discharging process of negative electrode-free lithium batteries, the deposition and stripping process of lithium metal on the negative electrode current collector is uneven, which can easily lead to irregular growth of lithium dendrites, and then cause the rupture and regrowth of the SEI film, continuously consume active lithium and aggravate harmful side reactions at the interface; lithium dendrites may also pierce the battery's diaphragm, causing internal short circuits, seriously affecting the safety and cycle life of the battery. Summary of the invention
[0004] Based on this, it is necessary to provide a composite current collector and a preparation method thereof, and a negative electrode-free lithium battery to improve the battery cycle performance.
[0005] The first aspect of the present invention is to provide a composite current collector, the scheme is as follows:
[0006] A composite current collector comprises a metal substrate and a first artificial SEI layer arranged on the metal substrate; the first artificial SEI layer comprises a high entropy alloy layer and an oxide solid electrolyte layer, the high entropy alloy layer is arranged between the metal substrate and the oxide solid electrolyte layer, the high entropy alloy layer contains a first high entropy alloy, and the oxide solid electrolyte layer contains a first oxide solid electrolyte; or, the first artificial SEI layer comprises a mixed ion-electronic conductive layer of a second high entropy alloy and a second oxide solid electrolyte.
[0007] In one embodiment, the material of the metal substrate is Cu.
[0008] In one embodiment, the first high entropy alloy or the second high entropy alloy contains at least 2 magnetic elements and at least 4 lithium-philic elements, the magnetic elements are selected from Fe, Co, Mn, Ni, Gd, Nd, Sm, and the lithium-philic elements are selected from Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi.
[0009] In one embodiment, the first oxide solid electrolyte or the second oxide solid electrolyte is selected from one or more of LLZO, Ta-doped LLZO, Ga-doped LLZO, W and Ta co-doped LLZO, Al and Mn co-doped LLZO, LLTO, LATP and LAGP.
[0010] In one embodiment, the thickness of the high entropy alloy layer is 10nm~30nm.
[0011] In one embodiment, the thickness of the oxide solid electrolyte layer is 10 nm to 30 nm.
[0012] In one embodiment, the composite current collector further includes a second artificial SEI layer, which is disposed on a side of the first artificial SEI layer away from the metal substrate, and a material of the second artificial SEI layer includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS.
[0013] In one embodiment, the thickness of the second artificial SEI layer is 10 nm to 30 nm.
[0014] The second aspect of the present invention is to provide a method for preparing a composite current collector according to any of the above embodiments, the scheme is as follows:
[0015] A method for preparing a composite current collector comprises the following steps:
[0016] providing a metal substrate;
[0017] A first artificial SEI layer is formed on the metal substrate; the first artificial SEI layer includes a high entropy alloy layer and an oxide solid electrolyte layer, the high entropy alloy layer is arranged between the metal substrate and the oxide solid electrolyte layer, the high entropy alloy layer contains a first high entropy alloy, and the oxide solid electrolyte layer contains a first oxide solid electrolyte; or, the first artificial SEI layer includes a mixed ion-electronic conductive layer of a second high entropy alloy and a second oxide solid electrolyte.
[0018] In one embodiment, the method for preparing the composite current collector further comprises the following steps:
[0019] A second artificial SEI layer is formed on a side of the first artificial SEI layer away from the metal substrate, and the material of the second artificial SEI layer includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS. The third aspect of the present invention is to provide a negative electrode-free lithium battery, the scheme is as follows:
[0020] A negative electrode-free lithium battery comprises a shell and the composite current collector, positive electrode, electrolyte and separator described in any one of the above embodiments arranged in the shell.
[0021] In one embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode layer arranged on the positive electrode current collector, the positive electrode material contained in the positive electrode layer includes an active material and a coating layer coating the active material, the active material includes a lithium-rich manganese-based material, and the material of the coating layer includes one or more of Li2FeSiO4 and Li2FeTiO4.
[0022] Compared with the conventional technology, the composite current collector and its preparation method, and the negative electrode-free lithium battery have the following beneficial effects:
[0023] The composite current collector and its preparation method form a first artificial SEI layer on a metal substrate. The first artificial SEI layer includes a high entropy alloy and an oxide solid electrolyte. The high entropy alloy can provide sufficient lithium-philic sites, induce the growth of lithium metal in the surface, and contribute to the dense deposition of lithium metal. The oxide solid electrolyte has excellent ion conductivity and can promote the rapid transport of lithium ions at the interface. The first artificial SEI layer helps to reduce the migration impedance of lithium ions at the interface and promotes its uniform nucleation growth in the horizontal direction, thereby improving the cycle electrochemical performance of the battery.
[0024] The above-mentioned negative electrode-free lithium battery has the above-mentioned composite current collector, and thus has corresponding technical characteristics and can obtain corresponding beneficial effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] FIG1 is a schematic structural diagram of a composite current collector according to an embodiment;
[0026] FIG. 2 is a schematic structural diagram of a composite current collector according to another embodiment.
[0027] Description of reference numerals:
[0028] 100, composite current collector; 110, metal substrate; 120, first artificial SEI layer; 121, high entropy alloy layer; 122, oxide solid electrolyte layer; 130, second artificial SEI layer; 200, composite current collector; 210, metal substrate; 220, first artificial SEI layer; 230, second artificial SEI layer. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0031] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0032] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0033] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0034] As shown in Fig. 1, a composite current collector 100 according to an embodiment of the present invention includes a metal substrate 110 and a first artificial SEI layer 120 disposed on the metal substrate 110. The first artificial SEI layer 120 includes a high entropy alloy layer 121 and an oxide solid electrolyte layer 122, wherein the high entropy alloy layer 121 is disposed between the metal substrate 110 and the oxide solid electrolyte layer 122, the high entropy alloy layer 121 includes a first high entropy alloy, and the oxide solid electrolyte layer 122 includes a first oxide solid electrolyte.
[0035] The composite current collector 100 forms a first artificial SEI layer 120 on the metal substrate 110. The first artificial SEI layer 120 includes a high entropy alloy layer 121 and an oxide solid electrolyte layer 122. The high entropy alloy can provide sufficient lithium-philic sites to induce the growth of lithium metal in the surface, which is conducive to the dense deposition of lithium metal. The oxide solid electrolyte has excellent ion conductivity and can promote the rapid transport of lithium ions at the interface. The first artificial SEI layer helps to reduce the migration impedance of lithium ions at the interface and promotes its uniform nucleation growth in the horizontal direction, thereby improving the cycle electrochemical performance of the battery.
[0036] Optionally, the material of the metal substrate 110 includes but is not limited to Cu.
[0037] In some examples, the first high entropy alloy contains at least 6 elements, for example, but not limited to, six or more of Fe, Co, Mn, Ni, Gd, Nd, Sm, Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi.
[0038] In some of the examples, the difference in molar proportions of different elements in the first high entropy alloy is within 5%.
[0039] In some examples, the first high entropy alloy comprises at least two magnetic elements and at least four lithium-loving elements, wherein the magnetic elements are selected from Fe, Co, Mn, Ni, Gd, Nd, and Sm, and the lithium-loving elements are selected from Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi.
[0040] In the above example, the first high entropy alloy contains at least 4 lithium-loving elements, and a certain content of lithium-loving elements can provide sufficient lithium-loving nucleation sites for lithium deposition. The first high entropy alloy also contains at least 2 magnetic elements, and a certain content of magnetic elements can generate a force perpendicular to the direction of the electric field, inducing the growth of lithium metal in the horizontal direction. The high entropy alloy layer can promote the horizontal diffusion and deposition behavior of lithium ions on its surface, inhibit the irregular growth of dendrites, and thus improve the cycle stability and safety performance of lithium batteries.
[0041] Illustratively, in a specific example, the first high entropy alloy includes Fe, Co, Nd, Al, Zn, Sn, and Sb.
[0042] Illustratively, in a specific example, the first high entropy alloy includes Fe, Co, Al, Zn, Sn and Mg.
[0043] Illustratively, in a specific example, the first high entropy alloy includes Ni, Gd, Sb, Ag, Au, and Si.
[0044] Exemplarily, in a specific example, the first high entropy alloy includes Nd, Sm, Al, Zn, Sn and Mg.
[0045] Illustratively, in a specific example, the first high entropy alloy includes Fe, Ni, Sb, Ag, Au, and Si.
[0046] Exemplarily, in a specific example, the first high entropy alloy includes Fe, Co, Ni, Zn, Sn, Mg, and Sb.
[0047] Exemplarily, in a specific example, the first high entropy alloy includes Fe, Co, Al, Zn, Sn, Mg, Sb and Ag.
[0048] The high entropy alloy layer 121 can be formed on the metal substrate 110 by a physical vapor deposition (PVD) process, such as a magnetron sputtering process or an evaporation process. In some examples, the high entropy alloy layer 121 is formed on the metal substrate 110 by a magnetron sputtering process, and the coating can be performed by using a HAE target and a direct current (DC) mode magnetron sputtering method. During the coating, the deposition chamber is evacuated to 2×10 -5 Pa~8×10 -5 Pa, introduce an inert gas (such as argon) with a flow rate of 20sccm~100sccm, control the working gas pressure to 0.1Pa~1Pa, and the working power to 20W~50W.
[0049] In some of the examples, the thickness of the high entropy alloy layer 121 is 10 nm to 30 nm. Further, in some of the examples, the thickness of the high entropy alloy layer 121 is, for example, 15 nm to 25 nm. In some specific examples, the thickness of the high entropy alloy layer 121 is 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, etc.
[0050] In some examples, the first oxide solid electrolyte is selected from one or more of LLZO (lithium lanthanum zirconium oxide), Ta-doped LLZO, Ga-doped LLZO, W and Ta co-doped LLZO, Al and Mn co-doped LLZO, LLTO (lithium lanthanum titanate), LATP (lithium aluminum titanium phosphate) and LAGP (lithium aluminum germanium phosphate). The above-mentioned first oxide solid electrolyte has excellent ion conductivity and can promote the transport of lithium ions at the interface.
[0051] The oxide solid electrolyte layer 122 can be formed on the high entropy alloy layer 121 by a physical vapor deposition process, such as a magnetron sputtering process or an evaporation process. In some examples, the oxide solid electrolyte layer 122 is formed on the high entropy alloy layer 121 by a magnetron sputtering process, and the film can be deposited by magnetron sputtering in a radio frequency (RF) mode, with the working gas pressure controlled to be 0.1Pa~1Pa and the working power to be 50W~100W.
[0052] In some examples, the thickness of the oxide solid electrolyte layer 122 is 10 nm to 30 nm. Further, in some examples, the thickness of the oxide solid electrolyte layer 122 is 15 nm to 25 nm. In some specific examples, the thickness of the oxide solid electrolyte layer 122 is, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, etc.
[0053] Studies have found that in humid air, Li2CO3 impurities are easily generated on the surface of oxide solid electrolytes, which will increase the interface impedance and make the solid electrolyte have poor wettability with Li.
[0054] To solve the above problems, in some examples, the composite current collector 100 is further provided with a second artificial SEI layer 130, which is provided on a side of the first artificial SEI layer 120 away from the metal substrate 110. The material of the second artificial SEI layer 130 includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS.
[0055] The material of the second artificial SEI layer 130 has water-oxygen stability, can protect the underlying oxide solid electrolyte, avoid the generation of Li2CO3 impurities, and improve the storage performance of the product. In addition, LiF has excellent electron isolation and certain lithium ion conductivity. MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2, and ZnS can undergo a substitution reaction with Li when the battery is charged to generate lithium ion-conducting inorganic substances and lithium-philic alloys.
[0056] In some examples, the material of the second artificial SEI layer 130 includes LiF and also includes one or more of MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2, and ZnS, so as to combine the above-mentioned multiple effects.
[0057] The second artificial SEI layer 130 can be formed on the oxide solid electrolyte layer 122 by a physical vapor deposition process, such as a magnetron sputtering process or an evaporation process. In some examples, the second artificial SEI layer 130 is formed on the oxide solid electrolyte layer 122 by a magnetron sputtering process, and the film can be deposited by a magnetron sputtering method in a radio frequency (RF) mode, with the working gas pressure controlled to be 0.1Pa~1Pa and the working power to be 20W~60W.
[0058] In some examples, the thickness of the second artificial SEI layer 130 is 10 nm to 30 nm. Further, in some examples, the thickness of the second artificial SEI layer 130 is 15 nm to 25 nm. In some specific examples, the thickness of the second artificial SEI layer 130 is, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, etc.
[0059] As shown in Fig. 2, a composite current collector 200 according to another embodiment of the present invention includes a metal substrate 210 and a first artificial SEI layer 220 disposed on the metal substrate 210. The first artificial SEI layer 220 includes a mixed ion-electron conductive layer of a second high entropy alloy and a second oxide solid electrolyte.
[0060] The composite current collector 200 forms a first artificial SEI layer 220 on the metal substrate 210, and the first artificial SEI layer 220 includes a mixed ion electronic conductive layer of a second high entropy alloy and a second oxide solid electrolyte. The high entropy alloy can provide sufficient lithium-philic sites, induce the growth of lithium metal in the surface, and contribute to the dense deposition of lithium metal. The multi-component SEI layer can promote the rapid transport of lithium ions at the interface. The first artificial SEI layer helps to reduce the migration impedance of lithium ions at the interface, and promotes its uniform nucleation growth in the horizontal direction, thereby improving the cycle electrochemical performance of the battery.
[0061] Optionally, the material of the metal substrate 210 includes but is not limited to Cu.
[0062] In some examples, the second high entropy alloy contains at least 6 elements, for example, but not limited to, six or more of Fe, Co, Mn, Ni, Gd, Nd, Sm, Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi.
[0063] In some of the examples, the difference in the molar proportions of different elements in the second high entropy alloy is within 5%.
[0064] In some examples, the second high entropy alloy comprises at least two magnetic elements and at least four lithium-loving elements, wherein the magnetic elements are selected from Fe, Co, Mn, Ni, Gd, Nd, and Sm, and the lithium-loving elements are selected from Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi.
[0065] In the above example, the second high entropy alloy contains at least 4 lithium-loving elements, and a certain amount of lithium-loving elements can provide sufficient nucleation sites for lithium deposition. The second high entropy alloy also contains at least 2 magnetic elements, and a certain amount of magnetic elements can generate a force perpendicular to the direction of the electric field, inducing the growth of lithium metal in the horizontal direction.
[0066] Illustratively, in a specific example, the first high entropy alloy includes Fe, Co, Nd, Al, Zn, Sn, and Sb.
[0067] Illustratively, in a specific example, the second high entropy alloy includes Fe, Co, Al, Zn, Sn and Mg.
[0068] Illustratively, in a specific example, the second high entropy alloy includes Mn, Gd, Sb, Ag, Au, and Si.
[0069] Illustratively, in a specific example, the second high entropy alloy includes Nd, Sm, Al, Zn, Sn and Mg.
[0070] Illustratively, in a specific example, the second high entropy alloy includes Fe, Ni, Sb, Ag, Au, and Si.
[0071] Exemplarily, in a specific example, the second high entropy alloy includes Fe, Co, Ni, Zn, Sn, Mg, and Sb.
[0072] Illustratively, in a specific example, the second high entropy alloy includes Fe, Co, Al, Zn, Sn, Mg, Sb and Ag.
[0073] In some examples, the second oxide solid electrolyte is selected from one or more of LLZO, Ta-doped LLZO, Ga-doped LLZO, W and Ta co-doped LLZO, Al and Mn co-doped LLZO, LLTO, LATP and LAGP. The second oxide solid electrolyte has excellent ion conductivity and can promote the transport of lithium ions at the interface.
[0074] In some of the examples, the mass fraction of the second oxide solid electrolyte in the first artificial SEI layer 220 is 60% to 80%. Further, in some of the examples, the mass fraction of the second oxide solid electrolyte in the first artificial SEI layer 220 is 65% to 75%. In some specific examples, the mass fraction of the second oxide solid electrolyte in the first artificial SEI layer 220 is, for example, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, etc.
[0075] The first artificial SEI layer 220 may be formed on the metal substrate 210 by a physical vapor deposition process, such as a magnetron sputtering process or an evaporation process. In some examples, the first artificial SEI layer 220 is formed on the metal substrate 210 by a magnetron sputtering process. During the deposition, the deposition chamber is evacuated to 2×10 -5 Pa~8×10 -5 Pa, an inert gas (such as argon) with a flow rate of 20sccm~100sccm is introduced, the working gas pressure is controlled to be 0.1Pa~1Pa, the RF mode is used to sputter the oxide solid electrolyte target, and the working power is 20W~50W; and the DC mode is used to sputter the high entropy alloy target, and the working power is 20W~50W.
[0076] In some of the examples, the thickness of the first artificial SEI layer 220 is 10 nm to 50 nm. Further, in some of the examples, the thickness of the first artificial SEI layer 220 is 20 nm to 40 nm. In some specific examples, the thickness of the oxide solid electrolyte layer is, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, 50 nm, etc.
[0077] Studies have found that in humid air, Li2CO3 impurities are easily generated on the surface of oxide solid electrolytes, which will increase the interface impedance and make the solid electrolyte have poor wettability with Li.
[0078] To solve the above problems, in some examples, the composite current collector 200 is further provided with a second artificial SEI layer 230, and the second artificial SEI layer 230 is provided on a side of the first artificial SEI layer 220 away from the metal substrate 210. The material of the second artificial SEI layer 230 includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS.
[0079] The material of the second artificial SEI layer 230 has water-oxygen stability, can protect the underlying oxide solid electrolyte, avoid the generation of Li2CO3 impurities, and improve the storage stability of the product. The second artificial SEI layer helps to achieve interface stability and improve the electrochemical performance of the battery. In addition, LiF has excellent electron isolation and certain lithium ion conductivity. MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2, and ZnS can undergo a substitution reaction with Li when the battery is charged to generate lithium ion-conducting inorganic substances and lithium-philic alloys.
[0080] In some examples, the material of the second artificial SEI layer 230 includes LiF and also includes one or more of MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2, and ZnS, so as to combine the above-mentioned multiple effects.
[0081] In some examples, the second artificial SEI layer 230 includes a first sublayer and a second sublayer, the material of the first sublayer includes LiF, and the second sublayer includes one or more of MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2, and ZnS.
[0082] The second artificial SEI layer 230 can be formed on the oxide solid electrolyte layer by a physical vapor deposition process, such as a magnetron sputtering process or an evaporation process. In some examples, the second artificial SEI layer 230 is formed on the first artificial SEI layer 220 by a magnetron sputtering process, and the film can be deposited by a magnetron sputtering method in a radio frequency (RF) mode, with the working gas pressure controlled to be 0.1Pa~1Pa and the working power to be 20W~60W.
[0083] In some examples, the thickness of the second artificial SEI layer 230 is 10 nm to 30 nm. Further, in some examples, the thickness of the second artificial SEI layer 230 is 15 nm to 25 nm. In some specific examples, the thickness of the second artificial SEI layer 230 is, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, etc.
[0084] Furthermore, the present invention also provides a method for preparing the composite current collector of any of the above embodiments.
[0085] The preparation method of the composite current collector comprises the following steps:
[0086] providing a metal substrate;
[0087] A first artificial SEI layer is formed on a metal substrate; the first artificial SEI layer includes a high entropy alloy layer and an oxide solid electrolyte layer, the high entropy alloy layer is arranged between the metal substrate and the oxide solid electrolyte layer, the high entropy alloy layer contains a first high entropy alloy, and the oxide solid electrolyte layer contains a first oxide solid electrolyte; or, the first artificial SEI layer includes a mixed ion-electronic conductive layer of a second high entropy alloy and a second oxide solid electrolyte.
[0088] In some examples, the method for preparing the composite current collector further includes the following steps:
[0089] A second artificial SEI layer is formed on a side of the first artificial SEI layer away from the metal substrate, and a material of the second artificial SEI layer includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS.
[0090] Furthermore, the present invention also provides a negative electrode-free lithium battery.
[0091] A negative electrode-free lithium battery in one embodiment comprises a housing and a composite current collector, a positive electrode plate, an electrolyte and a separator according to any of the above embodiments arranged in the housing. The separator is arranged between the composite current collector and the positive electrode plate.
[0092] Since the lithium source of the negative electrode-free lithium battery comes from the positive electrode active material, the positive electrode uses a lithium-rich manganese-based material containing a lot of active lithium, which can replenish lithium and improve battery performance.
[0093] The general chemical formula of lithium-rich manganese-based materials is xLiMO2•(1-x)Li2MnO3. Wherein, M is selected from transition metal elements such as Mn, Ni, and Co. Exemplarily, lithium-rich manganese-based materials include but are not limited to Li 1.2 Ni 0.2 Mn 0.6 O2、Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2、Li 1.186 Mn 0.54 Ni 0.131 Co 0.13 Nb 0.03 O 2.1 , Li 1.15 Ni 0.375 Ti 0.375 Mo 0.1 O2、Li 1.15 Ni 0.45 Ti 0.3 Mo 0.1 O 1.85 F 0.15 , Li 1.133 Mn0.467 Ni 0.2 Co 0.2 O 1.95 F 0.05 .
[0094] Lithium-rich manganese-based materials will undergo violent side reactions with the electrolyte under high voltage, resulting in battery cell capacity decay. To solve the above problems, in some examples, the positive electrode plate includes a positive electrode current collector and a positive electrode layer disposed on the positive electrode current collector. The positive electrode material contained in the positive electrode layer includes an active material and a coating layer coating the active material. The active material includes a lithium-rich manganese-based material, and the material of the coating layer includes one or more of Li2FeSiO4 and Li2FeTiO4. The material of the above coating layer has a high theoretical gram-specific capacity, excellent oxidation resistance, and structural stability, and can prevent the lithium-rich manganese-based material from having violent side reactions with the electrolyte under high voltage.
[0095] The coating layer can be formed on the lithium-rich manganese-based material by a physical vapor deposition process, such as a magnetron sputtering process or an evaporation process. In some examples, the coating layer is formed on the ion-electron lithium-rich manganese-based material by a magnetron sputtering process. During the coating process, the deposition chamber is evacuated to 2×10 -5 Pa~8×10 -5 Pa, introduce an inert gas (such as argon) with a flow rate of 20sccm~100sccm, control the working gas pressure to 0.1Pa~1Pa, and the working power to 20W~80W.
[0096] In some of the examples, the coating layer has a thickness of 5 nm to 60 nm. Further, in some of the examples, the coating layer has a thickness of 10 nm to 40 nm. In some specific examples, the coating layer has a thickness of, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 40 nm, 50 nm, 60 nm, etc.
[0097] It is understood that the positive electrode layer may further include a binder, a conductive agent, etc. The mass fraction of the binder in the positive electrode slurry is, for example, 2.0% to 10.0%. The mass fraction of the conductive agent in the positive electrode slurry is, for example, 2.0% to 10.0%.
[0098] Exemplarily, the binder includes one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, epoxy resin and nylon. Exemplarily, the conductive agent includes one or more of graphite, carbon black, acetylene black and Ketjen black.
[0099] Exemplarily, the material of the diaphragm is, for example, a polyethylene diaphragm, a polypropylene diaphragm, a polyvinylidene fluoride diaphragm, or a glass fiber diaphragm.
[0100] The electrolyte includes a solvent and a lithium salt dispersed in the solvent. Exemplarily, the lithium salt includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiBOB, LiDFOB, LiFSI and LiTFSI. Exemplarily, the solvent includes one or more of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl formate, ethyl formate, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, ethyl butyrate and propyl butyrate.
[0101] It is understood that the electrolyte may further include additives, such as fluoroethylene carbonate, vinylene carbonate, chloroethylene carbonate, fluoropropane trimethoxysilane, and the like.
[0102] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.
[0103] Example 1
[0104] This embodiment provides a composite current collector and a preparation method thereof.
[0105] The preparation method for the composite current collector of this embodiment comprises the following steps:
[0106] Step 1, providing a Cu foil with a thickness of 9µm as a metal substrate.
[0107] Step 2: deposit a high entropy alloy layer on both sides of the metal substrate by magnetron sputtering. Specifically, the Cu foil is transferred to a magnetron sputtering chamber, and the chamber is first evacuated to 4×10 -5 Pa, Ar gas is introduced with a flow rate of 60 sccm, the working gas pressure is controlled to be 0.4 Pa, the power is 40 W, and FeCoNdAlZnSnSb high entropy alloy is deposited on both sides of the metal substrate by direct current (DC) magnetron sputtering to form a high entropy alloy layer with a thickness of 20 nm.
[0108] Step 3: deposit an oxide solid electrolyte layer on the high entropy alloy layer by magnetron sputtering. Specifically, the working gas pressure is controlled to be 0.5 Pa, the power is 60 W, and LLZO is deposited on the high entropy alloy layer by radio frequency (RF) magnetron sputtering to form an oxide solid electrolyte layer with a thickness of 20 nm.
[0109] Step 4: deposit a second artificial SEI layer on the oxide solid electrolyte layer by magnetron sputtering. Specifically, the working gas pressure is controlled to be 0.2 Pa, the power is 50 W, and LiF is deposited on the oxide solid electrolyte layer by radio frequency (RF) magnetron sputtering to form a second artificial SEI layer with a thickness of 20 nm.
[0110] Example 2
[0111] The steps of this embodiment are basically the same as those of Embodiment 1, with the only difference being that in Step 2, the composition of the deposited high entropy alloy layer is FeCoNdAlSiSnSb.
[0112] Example 3
[0113] The steps of this embodiment are basically the same as those of embodiment 1, with the only difference being that in step 3, the composition of the deposited oxide solid electrolyte layer is Ta-LLZO.
[0114] Example 4
[0115] The steps of this embodiment are basically the same as those of embodiment 1, with the only difference being that in step 3, the composition of the deposited oxide solid electrolyte layer is Ga-LLZO.
[0116] Example 5
[0117] The steps of this embodiment are basically the same as those of embodiment 1, with the only difference being that in step 3, the component of the deposited oxide solid electrolyte layer is LATP.
[0118] Example 6
[0119] The steps of this embodiment are basically the same as those of embodiment 1, except that in step 3, the component of the deposited oxide solid electrolyte layer is LAGP.
[0120] Example 7
[0121] The steps of this embodiment are basically the same as those of Embodiment 1, except that in step 3, the component of the deposited second artificial SEI layer is MgF2.
[0122] Example 8
[0123] The steps of this embodiment are basically the same as those of embodiment 1, except that, in step 3, a second artificial SEI layer is deposited on the oxide solid electrolyte layer by a magnetron sputtering process. Specifically, the working gas pressure is controlled to be 0.2 Pa, the power is 50 W, and MgF2 with a thickness of 10 nm is deposited on the oxide solid electrolyte layer by radio frequency (RF) magnetron sputtering, and then LiF with a thickness of 10 nm is deposited to form the second artificial SEI layer.
[0124] Example 9
[0125] This embodiment provides a composite current collector and a preparation method thereof.
[0126] The preparation method for the composite current collector of this embodiment comprises the following steps:
[0127] Step 1, providing a Cu foil with a thickness of 9µm as a metal substrate.
[0128] Step 2: Deposit the first artificial SEI layer on both sides of the metal substrate by magnetron sputtering. Specifically, transfer the Cu foil into a magnetron sputtering chamber and evacuate the chamber to 4×10 -5 Pa, Ar gas was introduced with a flow rate of 60 sccm, the working gas pressure was controlled at 0.5 Pa, and the LLZO oxide electrolyte target was sputtered in radio frequency (RF) mode with a power of 70 W; and the FeCoNdAlZnSnSb high entropy alloy target was sputtered in direct current (DC) mode with a power of 30 W to form the first artificial SEI layer containing a mixed LLZO oxide electrolyte and FeCoNdAlZnSnSb high entropy alloy with a thickness of 40 nm, wherein the mass fraction of LLZO electrolyte was 70%.
[0129] Step 3: deposit a second artificial SEI layer on the first artificial SEI layer by magnetron sputtering. Specifically, the working gas pressure is controlled to be 0.2 Pa, the power is 50 W, and LiF is deposited on the first artificial SEI layer by radio frequency (RF) magnetron sputtering to form a second artificial SEI layer with a thickness of 20 nm.
[0130] Comparative Example 1
[0131] In this comparative example, Cu foil was used as the current collector.
[0132] The composite current collectors prepared in the above Examples 1 to 9 and Comparative Example 1 are applied to prepare negative electrode-free lithium batteries.
[0133] Specifically, the negative electrode-free lithium battery is prepared according to the following steps.
[0134] Step 1, preparation of positive electrode sheet:
[0135] The granular lithium-rich manganese-based material Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2 was transferred to the magnetron sputtering chamber and the chamber was first evacuated to 4×10 -5 Pa, introduce Ar gas with a flow rate of 60sccm, control the working gas pressure to 0.5Pa, and the power to 50W, deposit Li2FeSiO4 on the surface of the above-mentioned granular lithium-rich manganese-based material to form a coating layer with a thickness of 15nm to obtain the positive electrode material.
[0136] The positive electrode material, binder PVDF and conductive agent SP were weighed at a mass ratio of 80:10:10, added into NMP (N-methylpyrrolidone) solvent for homogenization and mixing to obtain positive electrode slurry.
[0137] The positive electrode slurry is coated on the surface of the aluminum current collector and dried to obtain a positive electrode sheet.
[0138] Step 2, preparation of electrolyte:
[0139] FEC (fluoroethylene carbonate) and DEC (diethyl carbonate) were measured at a volume ratio of 1:2 and mixed to obtain a mixed solvent. Lithium salts LiDFOB (lithium difluorooxalatoborate) and LiBF4 (lithium tetrafluoroborate) were dissolved in the mixed solvent, and the concentrations of LiDFOB and LiBF4 were both 0.6 mol / L. TTS (trifluoropropane trimethoxysilane) was then added at a mass fraction of 2% to prepare an electrolyte.
[0140] Step 3, assembly of negative electrode-free lithium battery:
[0141] The composite current collector prepared in the above-mentioned embodiments and comparative examples is assembled with a positive electrode sheet, a glass fiber separator and an electrolyte to obtain a negative electrode-free lithium battery.
[0142] Comparative Example 2
[0143] The difference between this comparative example and comparative example 1 is that the preparation process of the positive electrode sheet is as follows:
[0144] The untreated lithium-rich manganese-based material Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2, PVDF and SP are added into NMP (N-methylpyrrolidone) solvent in a mass ratio of 80:10:10 for homogenization and mixing, coated on the surface of aluminum current collector and dried to obtain the positive electrode sheet.
[0145] Comparative Example 3
[0146] The difference between this comparative example and Example 1 is that no oxide solid electrolyte layer is deposited on the composite current collector, that is, step 3 is not performed.
[0147] Difference 2 is that the preparation process of the positive electrode sheet is as follows:
[0148] The untreated lithium-rich manganese-based material Li 1.2 Ni 0.13 Mn 0.54 Co 0.13O2, PVDF and SP are added into NMP (N-methylpyrrolidone) solvent in a mass ratio of 80:10:10 for homogenization and mixing, coated on the surface of aluminum current collector and dried to obtain the positive electrode sheet.
[0149] The prepared negative electrode-free lithium battery was subjected to room temperature cycle test under 0.5C / 0.5C charge and discharge conditions, and the number of cycles when the battery capacity decayed to 80% of the initial capacity was recorded.
[0150] The test results are shown in Table 1.
[0151] Table 1 Cycling performance of lithium battery without negative electrode
[0152]
[0153] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0154] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A composite current collector, characterized in that: It includes a metal substrate and a first artificial SEI layer arranged on the metal substrate; the first artificial SEI layer includes a high entropy alloy layer and an oxide solid electrolyte layer, the high entropy alloy layer is arranged between the metal substrate and the oxide solid electrolyte layer, the high entropy alloy layer includes a first high entropy alloy, and the oxide solid electrolyte layer includes a first oxide solid electrolyte; or, the first artificial SEI layer includes a mixed ion-electronic conductive layer of a second high entropy alloy and a second oxide solid electrolyte; The first high entropy alloy or the second high entropy alloy comprises at least two magnetic elements and at least four lithium-loving elements, wherein the magnetic elements are selected from Fe, Co, Mn, Ni, Gd, Nd, and Sm, and the lithium-loving elements are selected from Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi; The composite current collector also includes a second artificial SEI layer, which is arranged on a side of the first artificial SEI layer away from the metal substrate, and the material of the second artificial SEI layer includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS.
2. The composite current collector according to claim 1, characterized in that: The material of the metal substrate is Cu.
3. The composite current collector according to claim 1, characterized in that: The first oxide solid electrolyte or the second oxide solid electrolyte is selected from one or more of LLZO, Ta-doped LLZO, Ga-doped LLZO, W and Ta co-doped LLZO, Al and Mn co-doped LLZO, LLTO, LATP and LAGP.
4. The composite current collector according to claim 1, characterized in that: The thickness of the high entropy alloy layer is 10nm to 30nm; and / or The thickness of the oxide solid electrolyte layer is 10nm~30nm.
5. The composite current collector according to claim 1, characterized in that: The thickness of the second artificial SEI layer is 10 nm to 30 nm.
6. A method for preparing a composite current collector, characterized in that: The following steps are involved: providing a metal substrate; A first artificial SEI layer is formed on the metal substrate; the first artificial SEI layer comprises a high entropy alloy layer and an oxide solid electrolyte layer, the high entropy alloy layer is arranged between the metal substrate and the oxide solid electrolyte layer, the high entropy alloy layer comprises a first high entropy alloy, and the oxide solid electrolyte layer comprises a first oxide solid electrolyte; or, the first artificial SEI layer comprises a mixed ion-electronic conductive layer of a second high entropy alloy and a second oxide solid electrolyte; The first high entropy alloy or the second high entropy alloy comprises at least two magnetic elements and at least four lithium-loving elements, wherein the magnetic elements are selected from Fe, Co, Mn, Ni, Gd, Nd, and Sm, and the lithium-loving elements are selected from Al, Zn, Sn, Mg, Sb, Ag, Au, Si, and Bi; The composite current collector also includes a second artificial SEI layer, which is arranged on a side of the first artificial SEI layer away from the metal substrate, and the material of the second artificial SEI layer includes one or more of LiF, MgO, ZnO, SiO2, Al2O3, Bi2O3, MgF2 and ZnS.
7. A negative electrode-free lithium battery, characterized in that: The invention comprises a shell and a composite current collector according to any one of claims 1 to 5, a positive electrode sheet, an electrolyte and a separator arranged in the shell, wherein the separator is arranged between the composite current collector and the positive electrode sheet.
8. The negative electrode-free lithium battery according to claim 7, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode layer arranged on the positive electrode current collector. The positive electrode material contained in the positive electrode layer includes an active material and a coating layer coating the active material. The active material includes a lithium-rich manganese-based material, and the material of the coating layer includes one or more of Li2FeSiO4 and Li2FeTiO4.
Citation Information
Patent Citations
Copper-based current collector and preparation method and application thereof
CN117039002A
KR20240072954A